Prolonged Gestation due to Mummified Fetuses in Conjunction with Normal Fetus in Barbari Doe - Mahajan, Mohit; Prasad, Shiv; Singh, Vipin; Tevatia, Gourav S.; Verma, Prashant (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The hypothalamus pituitary adrenal axis of the fetus is the prime pathway for initiation of parturition and  corticotropin-releasing factor (CRF) plays a central role in  the stress response for regulating this axis. Lefebvre (2015)  revealed pathological conditions such as mummification,  maceration, mucometra, hydrometra and pyometra altered  the normal function of the hypothalamic pituitary adrenal  axis, prolonging gestation and alternating the normal  physiology of the dam. Mummification is a sequel of foetal  death without abortion, often after ossification of bones, and  the resorption of the fetus is unfeasible (Noakes et al., 2009;  Chaudhari and Dabas, 2018). The incidence of mummification  (4%) is reported to be the highest among other gestational  disorders (Vikram et al. 2020) and is rarely recorded in does  and ewes. Mummification is associated with four major  infectious causes Toxoplasmosis, Chlamydophila, Border  disease (Pestivirus) and Coxiella Brunetti (Edmondson et al.,  2012; Lefebvre, 2015). Non-infectious causes of mummification  include traumatic injury to the fetus (Broaddus et al. 2009;  Dubey 2009), umbilical cord compression (Mahajan and  Sharma, 2002), uterine torsion, defective placentation (Irons,  1999), genetic anomalies, abnormal hormonal profiles and  chromosomal abnormalities. Protein and energy deficiency  during advance gestation may lead to fatal mummification  with animals clinically appearing weak and anemic (Lefebvre,  2015).
Keywords: Prolonged Gestation; Mummified Fetuses; Conjunction; Barbari Doe